Faktor yang Mempengaruhi Sikap Pengguna Terhadap Produk Halal di Malaysia - Azzamurni Bt Mohtar; Siti Muyassarah Binti Abd Nasir (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study purpose to examine the factors influencing consumer attitudes towards the branding of halal products, with a focus on knowledge about halal products, health as a priority, and the role of the halal logo in influencing consumer attitudes towards purchasing Ayam Bismi. A mixed-method approach is used in this study, involving a combination of quantitative and qualitative methods. Document analysis of surveys and observations is employed to obtain the study’s findings. Overall, the study found that the halal logo has a significant positive relationship with consumer attitudes towards the intention to purchase halal products, especially Ayam Bismi. The halal logo is identified as a crucial factor in influencing consumer attitudes towards halal products, helping to reduce doubts about the halal status of the product. The study’s findings indicate a positive relationship among all examined factors, providing evidence that the presence of the halal logo has a positive influence on consumer attitudes and purchase intentions